Biodosimetry testing of a simplified computational model for the UV disinfection of wastewater. Issue 1 (1st January 2006) - Templeton, M R; Hofmann, R; Andrews, R C; Whitby, G E
Abstract : A simplified computational model of the ultraviolet (UV) disinfection dose delivered to wastewater was developed and the model outputs were compared with pilot-scale biodosimetry data. The model assumed plug flow, an assumption that may apply for some open channel UV reactors designed for wastewater disinfection and in which case may eliminate the need for involved and expensive computational fluid dynamics analyses of flow patterns. The reactor residence times derived from this assumption were combined with the output from a two-dimensional, point-source summation UV irradiance model to calculate UV dose. The output from the irradiance model was adapted to account for the cross-sectional distribution of UV irradiance within the reactor. Two UV reactor configurations were modeled and pilot-tested at two UV transmittance (UVT) values that are typical for wastewater. The simplified model predicted doses that fell within the range of the observed UV doses under some flow and UVT conditions, however it did so inconsistently and over-predicted the doses at the highest tested flow rates. This was concluded to be due to a breakdown of the simplified plug flow assumption due to deviations in the velocity field distribution at higher flows. Therefore, while this modeling approach may provide "back of the envelope" initial estimates of the UV doses supplied to wastewater and may allow a qualitative evaluation of the effect of adjusting UV reactor design parameters (e.g., channel width, lamp spacing) on the resulting UV dose, the precise quantitative prediction of UV dose must continue to rely on more sophisticated models. Key words : ultraviolet disinfection, computational modeling, wastewater treatment.